Chile : Fostering Technology Transfer and Commercialization - World Bank (Washington, DC, 2013)
Chile is an economy rich in natural resources and their efficient exploitation has proved the right strategy to grow successfully over the last few decades. More recently, in the broader context of increasing globalization and competitive pressures, it has chosen as its main development driver the contribution that arises from innovation and the adoption of higher levels of technology to enhance productivity growth and to add to national competitiveness. There is strong public commitment to increase funding to stimulate innovation, but improvements in the technology transfer and commercialization system will not only involve an increase in funding but also changes in incentives, funding reallocations and institutional building. This report responds to a request by the CNIC (National Innovation Council for Competitiveness - Consejo Nacional de Innovacion para la Competitividad), through its Secretariat, to review Chile´s knowledge/technology transfer and commercialization system and identify practical steps to accelerate the development of an effective and dynamic system. The overall objective is to expand the number of firms in Chile that use knowledge as its main competitive strategy. The remainder of the report is structured as follows. Chapter two conducts a diagnostic of Chile's current system, and chapter three provides recommendations to upgrade technology transfer and commercialization practices and incentives in Chile considering its current endowments and lessons learned from international reference models. Chapter four summarizes the conclusions of the review.